Residential Conditions of Immigrants in Andalusia (spain) (Andamios, Revista de Investigación Social, 2013)
This paper analyzes the residential conditions of immigrants in Spain. Drawing on the concepts of living and housing measure the situation from the indicators of stability, adaptation, livability and accessibility. Data were obtained from the application of a 1738 housing survey and registration of expert housing conditions. The results show a poor housing situation, which affected differently depending on the origin of immigrants.
Keywords: Andalusia; Immigrants; Adequacy; Accessibility; Stability; Habitability